2019
DOI: 10.1590/rbz4820180028
|View full text |Cite
|
Sign up to set email alerts
|

Additional feeding during late gestation improves initial litter weight of lactating sows exposed to high ambient temperature

Abstract: The present study investigated the impacts of additional feeding (AF; containing 16% excess feed than control diet in the last two weeks of gestation) during late gestation period and different backfat thickness (BFT) including low (<20 mm) and high (≥20 mm) backfat on reproductive performance, litter size, blood metabolites, hormonal profiles, colostrum, and milk composition of sows from day 90 of gestation to farrowing, and from farrowing to weaning during summer (average 28.3 °C). Fiftyfour crossbred sows (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The goal is to provide the gestating sow with the extra energy and amino acids needed in late gestation to support the conceptus's exponential growth [22]. Increasing the average daily feed intake (ADFI) in the later stages of pregnancy contributes to mammary gland development, milk production [23,24], fetal growth [25,26], and the development of piglet thermoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to provide the gestating sow with the extra energy and amino acids needed in late gestation to support the conceptus's exponential growth [22]. Increasing the average daily feed intake (ADFI) in the later stages of pregnancy contributes to mammary gland development, milk production [23,24], fetal growth [25,26], and the development of piglet thermoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of high SF diets on farrowing duration may be due to the increased constipation index. Gestating sows, in particular, are at risk of constipation due to a restricted diet from 2 d before the expected parturition ( Choi et al., 2019 ; Oliviero et al., 2009 ). Constipation adversely affects sows health by increasing distress symptoms, gut obstruction, and prolonged farrowing duration ( Thorsen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of the HF diets on farrowing duration can be because of a higher constipation index. Practically, the feed intake of gestating sows is restricted during the last 2 days before the expected farrowing [21]. In this situation, the probability of occurring constipation increases around farrowing due to low feed intake and ber intake [14,43].…”
Section: Discussionmentioning
confidence: 99%
“…The improved intestinal integrity during gestation may re ect in the lactation period with greater potential for digestibility of nutrients and possibly more e cient digestion. Particularly that the feed intake of lactating sows is almost two times higher than gestating sows and even a small increase of dietary ber level may induce further stress and compromise litter performance [21]. It has been reported that brous diets increase the frequency of meals, spent time eating, and decreased lying time [9].…”
Section: Introductionmentioning
confidence: 99%